2015
DOI: 10.1371/journal.pone.0119594
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphatase PPN1 of Saccharomyces cerevisiae: Switching of Exopolyphosphatase and Endopolyphosphatase Activities

Abstract: The polyphosphatase PPN1 of Saccharomyces cerevisiae shows an exopolyphosphatase activity splitting phosphate from chain end and an endopolyphosphatase activity fragmenting high molecular inorganic polyphosphates into shorter polymers. We revealed the compounds switching these activities of PPN1. Phosphate release and fragmentation of high molecular polyphosphate prevailed in the presence of Co2+ and Mg2+, respectively. Phosphate release and polyphosphate chain shortening in the presence of Co2+ were inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The most high-molecular weight polyP was not hydrolyzed even after 120-min incubation. Thus, the recombinant PPX1 had no endopolyphosphatase activity, in contrast to PPN1 [33].…”
Section: Properties Of Recombinant Ppx1mentioning
confidence: 91%
See 1 more Smart Citation
“…The most high-molecular weight polyP was not hydrolyzed even after 120-min incubation. Thus, the recombinant PPX1 had no endopolyphosphatase activity, in contrast to PPN1 [33].…”
Section: Properties Of Recombinant Ppx1mentioning
confidence: 91%
“…The yeast polyphosphatase PPN1 is inhibited by ATP and stimulated by ADP [33]. The effects of AMP, ADP and ATP on the activity of the recombinant PPX1 with polyP 15 as a substrate were insignificant ( Table 3).…”
Section: Properties Of Recombinant Ppx1mentioning
confidence: 99%
“…Reaction end products are P i and P 3 , whereas PP i is a potent inhibitor [42]. A recent study has revealed that, depending on the reaction conditions, Ppn1 acts preferentially as endo-or exopolyphosphatase and its endopolyphosphatase activity is inhibited by ATP, but activated by ADP [43].…”
Section: The Endopolyphosphatase Ppn1mentioning
confidence: 99%
“…The exopolyphosphatase PPX1 of S. cerevisiae hydrolyzes adenosine-tetraphosphate phosphohydrolase and guanosine-tetraphosphate phosphorhydrolase activities [14]. The polyphosphatase PPN1 (http://www.uniprot.org/uniprot/Q04119) of S. cerevisiae degrades PolyP both by cleaving Pi from the chain end and by fragmenting long-chain polymers into shorter ones [15] [16]. Pi release was predominant in the presence of Co 2+ , while the fragmentation of high-molecular PolyP was predominant in the presence of Mg 2+ [16].…”
Section: Introductionmentioning
confidence: 99%
“…The polyphosphatase PPN1 (http://www.uniprot.org/uniprot/Q04119) of S. cerevisiae degrades PolyP both by cleaving Pi from the chain end and by fragmenting long-chain polymers into shorter ones [15] [16]. Pi release was predominant in the presence of Co 2+ , while the fragmentation of high-molecular PolyP was predominant in the presence of Mg 2+ [16]. No other substrates of this enzyme are known; the pyrophosphatase activity of PPN1 was extremely low [17].…”
Section: Introductionmentioning
confidence: 99%